A time series analysis of determinants of FDI in Afghanistan: which one matters the most, security or economic growth? / Abdul Fareed Delawari - Delawari, Abdul Fareed (Universiti Teknologi MARA Selangor, 2018)
Afghanistan has been practicing market economic system since 2002. Since then, the government has been initiating different policies and announced various incentives to attract foreign direct investment (FDI) to the country. However, the outcome has not been satisfactory due to several political and economic factors. This paper explores the relationship between security, economic growth and FDI in Afghanistan, using ARDL model. The paper covers a period from 2002 to 2016. The empirical results of this study show that there is a negative long-term relationship between security and FDI. Hence, the author concludes that, to attract FDI to the country, insuring security should be the top priority of the government of Afghanistan.